STOCK VALUATION MENGGUNAKAN DIVIDEND DISCOUNTED MODEL (DDM) DALAM PENGAMBILAN KEPUTUSAN INVESTASI PADA BANK PEMBANGUNAN DAERAH YANG TERDAFTAR DI BURSA EFEK INDONESIA - Chairil Affandy (UNIB Press, 2019)
This study aims to find out the intrinsic value of each share of regional development banks listed on the IDX. This study also aims to find out the stock market price (closing price) is below or above the intrinsic value of its shares. Finally, this study aims to find out which bank shares are the best to choose as investment options. This research was conducted in a one-year period, 2017. This type of research is descriptive research with quantitative methods. Descriptive research is research that seeks to describe or describe data that has been collected as it is. This study uses secondary data. Secondary data used in the form of data collected during the period in the form of numerical data contained in the annual report banking obtained from the official website of Indonesia Stock Exchange. In this study, the researcher described the reasonableness condition (value) of the stock price analyzed using the DDM method of model constant growth. This study reveals: (1) the intrinsic value of the shares of the Regional Development Bank in the Indonesia Stock Exchange evaluated by the DDM method of constant growth are as follows, the intrinsic value of BJBR shares is Rp 2455.25; while BJTM is Rp 810.67; (2) the intrinsic value of BJBR and BJTM in 2017 is below the market price, which means that the two regional development banks are considered undervalued, and the decision taken is bought, or held if it's already owned; (3) BJBR shares are the best shares to be chosen as investment options compared to BJTM, because BJBR has the highest difference between intrinsic value at its market price.